PENGARUH MODEL PEMBELAJARAN THINK PAIR SHARE DAN MAKE A MATCH TERHADAP HASIL BELAJAR - Wilson Sitopu, Joni; Rosenta Purba, Ika; Frihatini, Emi (Jurnal Metabio, 2022)
The problems in this study are: The selection of learning models used by teachers is not varied, student activity is still lacking during teaching and learning activities, student absorption is low, teachers still often use the lecture model, so teacher explanations are still abstract. The purpose of this study is; To determine the effect of the think pair share and make a match learning models on the learning outcomes of grade VII students of Kartika 1-4 Private Junior High School Pematangsiantar. The research method is an experimental method with a Quasi Experiment Design. The research design is a Two Group Randomized Posttest-Only Control Design. After the initial test (pretest) was conducted in both classes, learning was carried out with different treatments. In the experimental class, learning was carried out using the Think Pair Share learning model, while in the control class, the Make A Match learning model was implemented. After the learning process was completed, a final test (posttest) was carried out. Based on the research analysis, it was obtained 1) the learning outcomes of students who used the Think Pair Share learning model were better than the learning outcomes of students who used the Make A Match learning model; 2) There was a difference in the improvement in the learning outcomes of students who used the Think Pair Share learning model and the improvement in the learning outcomes of students who used the Make A Match learning model; and 3) Student attitudes toward learning using the Think Pair Share and Make A Match learning models.